Chitosan/poly(γ-glutamic acid) nanoparticles incorporating IFN-γ for immune response modulation in the context of colorectal cancer. (24th June 2019) - Castro, Flávia; Pinto, Marta L.; Almeida, Rui; Pereira, Flávia; Silva, Andreia M.; Pereira, Catarina L.; Santos, Susana G.; Barbosa, Mário A.; Gonçalves, Raquel M.; Oliveira, Maria J.
Abstract : This work highlights the potential synergistic effect of chitosan/γ-PGA nanoparticles with immunomodulatory cytokines, like IFN-γ, for anticancer therapy. Abstract : IFN-γ therapy has been approved by the Food and Drug Administration (FDA) for the treatment of chronic granulomatous disease and severe malignant osteopetrosis. Despite the promising IFN-γ-based therapeutic applications, its limited success in clinical trials is related with limitations inherent to its molecular properties and with the difficulties to deliver it locally or with adequate periodicity to achieve a therapeutic effect. We have previously shown that chitosan (Ch)/poly(γ-glutamic acid) (γ-PGA) nanoparticles (NPs) are immunostimulatory, impairing colorectal cancer cell invasion. Ch is a biocompatible cationic polysaccharide extensively studied and already approved for biomedical applications while γ-PGA is a poly(amino acid), biodegradable and negatively charged. Here, we evaluated the potential of Ch/γ-PGA NPs as vehicles for IFN-γ and their ability to modulate immune cells' phenotype. In this study, Ch/IFN-γ/γ-PGA nanoparticles (IFN-γ-NPs) prepared by a co-acervation method, presenting a size of approximately 180 nm and a low polydispersity index, were tested for their immunomodulatory activity. These IFN-γ-NPs induced an immunostimulatory profile on dendritic cells (DCs) with increased cell surface costimulatory molecules and secretion of pro-inflammatory cytokines, including IL-6, IL-12p40 and TNF-α. IFN-γ-NPs also modulated the IL-10-stimulated macrophage profile, increasing their ability to secrete the pro-inflammatory cytokines IL-6, IL-12p40 and TNF-α. Concomitantly, these phenotypic alterations enhanced T cell proliferation. In addition, the ability of DCs and macrophages to induce colorectal cancer cell invasion was hampered in the presence of IFN-γ-NPs. Although the major observations were mediated by Ch/γ-PGA NPs, the incorporation of IFN-γ into NPs potentiated the expression of CD40 and CD86, and the impairment of colorectal cancer cell invasion. This work bridges the previously reported immunostimulatory capacity of Ch/γ-PGA NPs with their potential as carriers for immunomodulatory molecules, like IFN-γ, opening new avenues for their use in clinical settings.